Biodegradable polymeric blends of PHB and PLA for film production Blendas poliméricas biodegradáveis de PHB e PLA para fabricação de filmes - Pachekoski W.M. (2014)
Poly(hydroxybutyrate) - PHB - and poly(latic acid) - PLA - are thermoplastic polyesters with huge potential for industrial applications since they are fully biodegradable and can be processed by usual methods. However, due to their limited mechanical properties, they need to be modified to achieve better performance and become industrially competitive. The properties of both polymers and their mixtures were evaluated in order to investigate their application for thin films extrusion, for packages. PHB/PLA thin films were produced by extrusion and blow film techniques. To allow for an industrial production process, the preparation of the polymer blend should be changed in order to decrease their high adhesion during processing.